2016
DOI: 10.1016/j.geoforum.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Struggles over work take place at home: Women’s decisions, choices and constraints in the Tiruppur textile industry, India

Abstract: Article (Accepted Version) http://sro.sussex.ac.uk Carswell, Grace (2016) Struggles over work take place at home: women's decisions, choices and constraints in the Tiruppur textile industry, India. Geoforum, 77. pp. 134-145.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Thus, women withdrawing from the workforce has been 'viewed as a symbol of status and upward mobility in India'. Rao (2014) and Carswell (2016) using case studies of women working in rural south India find that these highstatus production activities are deemed to reflect household status even among women from lower caste groups as their spouses' incomes increase and they are out of economic deprivation. This combined with residence in a joint family (where several generations co-reside) may impose more restrictions for women in terms of movements outside home, access to resources and decision-making capacity.…”
Section: Status and Autonomymentioning
confidence: 99%
“…Thus, women withdrawing from the workforce has been 'viewed as a symbol of status and upward mobility in India'. Rao (2014) and Carswell (2016) using case studies of women working in rural south India find that these highstatus production activities are deemed to reflect household status even among women from lower caste groups as their spouses' incomes increase and they are out of economic deprivation. This combined with residence in a joint family (where several generations co-reside) may impose more restrictions for women in terms of movements outside home, access to resources and decision-making capacity.…”
Section: Status and Autonomymentioning
confidence: 99%
“…Dalit women act on the basis of the same compulsions, impulses and rationales as others. We should also be alert to the fissures within the Dalit category along both caste and class lines (Carswell 2016). This constitutes a first step towards recognizing the agency and individuality of women.…”
Section: A Palace On a Dung-heapmentioning
confidence: 99%
“…She documents the rise of a patriarchal conservatism based on a male breadwinner model which runs counter to the radicalism of Dalit mobilization (Still 2014:16). Carswell (2016) likewise argues that Dalit women's withdrawal from paid work in Western Tamil Nadu "was clearly associated with strong socio-economic aspirations and a tightening of patriarchal controls" (p. 135). Still (2014) contends that this conservatism must be understood and analyzed in a wider social context, within which social status is mapped onto the behavior of women.…”
mentioning
confidence: 99%
“…This is definitely the case in the NCR, where our large and socially segmented reserve army of labour — mainly migratory — does not engage in acts of open resistance. However, our ‘classes of labour’ do develop their own different coping mechanisms, and engage in acts of ‘labour resilience’ (Katz, ), which span realms of production and reproduction (Carswell, ; Ruwanpura, ). Our fieldwork showed that, for instance, contract workers cheat ‘exclusive agreements’ with contractors by working for multiple parties.…”
Section: Non‐factory ‘Classes Of Labour’ In India: Multiple Forms Ofmentioning
confidence: 99%